RADIOFREQUENCY ABLATION IN THE TREATMENT OF OSTEOID OSTEOMA: A CASE SERIES - Nguyễn , Thị Huyền; Đàm, Thuỳ Trang; Phạm , Mạnh Cường (Tạp chí Điện quang & Y học hạt nhân Việt Nam, 2024)
Objective: Radiofrequency ablation (RFA) has emerged as a minimally invasive therapeutic option for osteoid osteoma (OO). Although extensively studied worldwide, data on its effectiveness and safety in Vietnam remain limited. This study presents a case series evaluating the technical success, clinical outcomes, and complications of RFA in OO treatment.Materials and Methods: Four male patients with OO underwent RFA over a three-month period. Lesions were located in the femur (n = 2) and tibia (n = 2). Two patients underwent primary RFA, while two received RFA after failed surgical treatment. Pain relief, recurrence rates, and complications were assessed over a 2-4 month follow-up period.Results: Three out of four patients achieved complete pain relief without recurrence or complications. One patient experienced recurrent pain four months post-procedure.Conclusion: RFA is a safe and effective minimally invasive treatment for OO, offering immediate symptom relief with a low recurrence rate. Further studies with larger sample sizes and longer follow-up are warranted to confirm these findings.